DEVELOPMENT OF COMMUNICATIVE DIDACTIC COMPETENCE OF HIGH SCHOOL STUDENTS - KUCHIMOVA NILYUFAR TURANBAYEVNA; TOKHIROVA SARVINOZ XUSENOVNA (International Journal of Innovations in Engineering Research and Technology, 2021)
Communicative competence is defined as the ability to interact effectively with others. At its most basic, competence is seen as a combination of language aptitudes an individual has for learning a foreign language. Such potential contributes to his/her attaining high levels of performance. This paper considers the following: the nature of communicative competence and some of its models; the importance of developing communicative competence among students; and the implications of communicative competence in English language teaching and learning.